Recovery of a dilated left ventricle after cessation of cocaine and HVAD™ explantation using a titanium plug. Issue 12 (8th November 2022) - Elbayomi, Mohamed; Weyand, Michael; Seitz, Timo; Heim, Christian; Steger, Katrin; Tandler, Rene
Abstract: The ultimate goal in the treatment of end‐stage heart failure is the recovery of cardiac function following mechanical assistance of the left ventricle. The HVAD™ pump (HeartWare Inc.) left ventricular assist device (LVAD) can be explanted without resternotomy. This article demonstrates that the use of a custom‐made mechanical plug (manufactured by INNOVO Solutions GmbH), which can be inserted into the LVAD's sewing ring, is feasible. This mechanical plug explicitly designed for device explantation is a viable alternative to the current standard of care. This article adopts a less invasive technique to explant the pump. The following case illustrates this technique.